Elucidating the Molecular Architecture of the 1D-AR:PDZ-Protein Macromolecular Complex - Harris, Dorathy-Ann Alyssa (My University, 2019)
G Protein-Coupled Receptors (GPCRs) are seven transmembrane proteins that are the targets for over 30% of all medications currently on the market. Adrenergic Receptors (ARs) are one type of GPCR that responds to the endogenous catecholamines norepinephrine (NE) and epinephrine(Epi). In the AR family, there are three types: 1-, 2-, and -ARs. Within each of these subfamilies are three subtypes and the Hague lab focuses one of these receptors: the 1D-AR. The 1D-AR is an interesting receptor in that it is very difficult to study due to its intracellular localization. There are no known cell lines that express endogenous 1D-ARs and within 48 hours after removing epithelial cell expressing the 1D-AR at the membrane, the receptor becomes localized to the endoplasmic reticulum (ER). Studying the 1D-AR is clinically important as there are many disorders that are influenced by this receptor. For example, it can impact urine flow in older males, due to benign prostate hypertrophy (BPH). The 1D-AR is also vital in the circulatory system in repairing blood vessels after injury as well as stimulus-induced movement. Also of note is the role the 1D-AR plays in both schizophrenia and post-traumatic stress disorder (PTSD, Raskind et. al. 2018). It has been noted that treatment with antagonists will decrease the reoccurrence of nightmares in veterans with PTSD. However, most antagonists have major toxic side effects that are associated with taking these medications. Thus, it is vital to determine how the 1D-AR signals with its PDZ and non PDZ proteins as a potential to create new therapeutics for PTSD, schizophrenia, BPH, and cardiovascular disease. Previously, the Hague laboratory determined that there may be a cell line that endogenously expresses the 1D-AR. Through mass spectrometry, it was determined that SW480 cells (a colorectal cancer cell line; CRC) express interacting proteins that have been previously shown to interact with the 1D-AR. Thus, I proposed to determine if this cell line does endogenously express the 1D-AR. Unfortunately, it was determined that the 1D-AR is not present in SW480 cells; instead the most common receptor discovered was the 1B-AR. This was apparently inconsistent with the only other paper (Masur et. al. 2001) that attempted to characterize the ARs present in SW480 cells and their role in cancer. When we attempted to use traditional methods, such as radioligand binding, we were also unable to detect this receptor. Thus, we concluded that the EPIC Dynamic Mass Redistribution (DMR) technology is able to detect previously imperceptible, low density receptors. The Hague laboratory has also determined that the 1D-AR must form a homodimeric macromolecular structure to even retain plasma membrane localization. Specifically, the 1D-AR interacts with the PSD95/DLG1/Zo-1 (PDZ) domain proteins syntrophin and Scribble (SCRIB) via a PDZ-ligand on its C-terminus (CT) in all human cell lines screened to date. This interaction was unique as no other GPCRs interacted with syntrophins or Scribble. Interestingly, in only one of the cell lines screened, it was also discovered that there are three additional proteins that interact with the 1D-AR. These proteins are calcium/calmodulin-dependent protein kinase (CASK), human disks large 1 (hDLG1), and LIN7A. Previous research has shown that hDLG1 and LIN7A can also associate with another membrane-associated guanylate kinase (MAGUK) protein, MPP7. Thus, I proposed to biochemically determine the architecture of the 1D-AR:PDZ protein complex and determine the functional purpose of these PDZ proteins. Based on our data, it appears that SCRIB binds the 1D-AR with the highest affinity (0.07 M), particularly PDZ domains 1/4 (0.78 and 1.38 M, respectively). Syntrophins bound with the next highest affinity (0.56 M) followed by hDLG1 (0.72 M). CASK did bind, but at very low affinity (2.13 M) and neither LIN7A nor MPP7 appeared to bind. It is yet unclear how the hDLG1 tripartite complex interacts with the 1D-AR, whether it be as a transport or scaffolding complex. All the PDZ proteins that seem to interact with the 1D-AR are basolateral proteins and involved in either scaffolding or localization. To determine which membrane the 1D-AR is actually localized to, we needed to find a reliable three-dimensional (3D) methodology to use as a model to conduct our experiments. I proposed to use several different methods; a hydrogel method (such as Corning Life Science’s Matrigel) and a non-adherent method (such as Corning Life Science’s Spheroid Microplate) to find the most consistent methodology for forming our 3D structures. Matrigel proved to be inconsistent for our model cell type; HEK293T cells. This is likely due to the length of time necessary to form the spheroid and lumen. However, the spheroid microplate proved to be efficient and fast in the formation of our spheroids. Interestingly, I noticed the 1D-AR at the surface of the membrane, something that is not seen in two-dimensional (2D) cells. I was determined to see if this correlated to an increase in pharmacodynamic properties, and indeed, it did show a significant increase in both EC50 and Emax. Our data, combined, seems to indicate an intricate macromolecular complex of PDZ and non-PDZ proteins that are vital for polarization of the cells and localization to the proper membrane. These data open a whole new field of questions in fundamental cell biology and open the door to novel therapeutics that can target any number of new sites.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: 3D Cell Modeling; Adrenergic Receptors; Dynamic Mass Redistribution; G Protein-Coupled Receptors; Pharmacology; 1D-AR; Molecular biology; Cellular biology; Pharmacology